Potential diagnostic value of PD‐1 in peripheral blood mononuclear cells of postmenopausal osteoporosis patients - Cai, Xiu‐Ping (J Clin Lab Anal, 2020)
BACKGROUND: Postmenopausal osteoporosis (PMOP) is an estrogen deficiency‐induced skeletal disorder. Bone mineral density (BMD) testing is the gold standard for diagnosing osteoporosis. However, its sensitivity for fracture risk assessment is low. Programmed cell death protein 1 (PD‐1) is a key immune checkpoint molecule implicated in the pathophysiology of bone remodeling, but its role in osteoporosis has not yet been explored. Thus, this study aimed to assess the expression and diagnostic utility of PD‐1 in PMOP. METHODS: A total of 56 patients with PMOP and 37 postmenopausal healthy controls (NC) were enrolled in the study. Peripheral blood mononuclear cells (PBMCs) were isolated by Ficoll density gradient centrifugation, and PD‐1 expression was measured by quantitative polymerase chain reaction (qPCR). Pearson's correlation test was performed to explore the associations between PD‐1 level and clinical variables, while receiver operating characteristic (ROC) curve analysis was used to evaluate the potential diagnostic value of PD‐1 in patients with PMOP. RESULTS: We found that PD‐1 level was significantly upregulated in the PBMCs of PMOP patients than those of NC (P = .016). PD‐1 expression was positively correlated with C‐reactive protein (CRP) levels. ROC curve analysis showed that PD‐1 had certain diagnostic value for PMOP (area under the curve = 0.65, standard error = 0.06, 95% confidence interval [0.53,0.76], P = .016), with a sensitivity and specificity of 44.64% and 81.08%, respectively. CONCLUSION: Programmed cell death protein 1 is significantly upregulated in the PBMCs of PMOP patients and has certain diagnostic value for PMOP.